The emerging role of circular RNAs in breast cancer. Issue 6 (25th June 2019) - Zhou, Si-ying; Chen, Wei; Yang, Su-jin; Xu, Zi-han; Hu, Jia-hua; Zhang, He-da; Zhong, Shan-liang; Tang, Jin-hai
Abstract : Breast cancer (BCa) is one of the most frequently diagnosed cancers and leading cause of cancer deaths among females worldwide. Circular RNAs (circRNAs) are a new class of endogenous regulatory RNAs characterized by circular shape resulting from covalently closed continuous loops that are capable of regulating gene expression at transcription or post-transcription levels. With the unique structures, circRNAs are resistant to exonuclease RNase R and maintain stability more easily than linear RNAs. Recently, an increasing number of circRNAs are discovered and reported to show different expression in BCa and these dysregulated circRNAs were correlated with patients' clinical characteristics and grade in the progression of BCa. CircRNAs participate in the bioprocesses of carcinogenesis of BCa, including cell proliferation, apoptosis, cell cycle, tumorigenesis, vascularization, cell invasion, migration as well as metastasis. Here we concentrated on biogenesis and function of circRNAs, summarized their implications in BCa and discussed their potential as diagnostic and therapeutic targets for BCa.